CASE REPORT: IMPROVEMENT IN BODY CONDITION SCORE (BCS) IN A CAT WITH DIARRHEA INFECTED WITH ANCYLOSTOMA SPP. - Stephanie Levina; Ida Ayu Dian Kusuma Dewi; I Nyoman Suartha (Buletin Veteriner Udayana, 2026)
An 8-month-old domestic male cat presented with chronic bloody diarrhea, accompanied by weight loss and a below-ideal body condition score (BCS) of 3/9. Fecal examination using native, sediment, and flotation methods confirmed infection with Ancylostoma spp., whereas hematological examination revealed leukocytosis with neutrophilia and monocytosis. Bacterial culture of the fecal sample yielded negative results. Treatment was administered with the anthelmintic drug Drontal Cat® (pyrantel pamoate and praziquantel), along with symptomatic therapy using kaolin–pectin, supportive therapy with B12, probiotics, and high-protein diet (Purina Pro Plan Kitten). Follow-up evaluation showed that by days 3 and 7, the patient no longer had diarrhea, and microscopic examination revealed no Ancylostoma spp. eggs in the stool. By week 4, the cat had gained weight to 3.2 kg and achieved an ideal BCS of 4/9. This case demonstrates that combination therapy can yield favorable outcomes and recovery, thereby improving the nutritional status and enhancing the quality of life of the cat.